The Trust Problem - Durand, E. Dana (Quarterly Journal of Economics, 1914)
I. Introductory. Definitions of trust, pool, industrial combination, 382. — Theory that elimination of unfair competition and special privileges would rob combinations of monopoly power, 383. — Difficulty of proof or disproof from experience, 385. — Power of pools to advance prices, 389. — Trust prices, 390. — Oil, sugar, tobacco and steel trusts, 391. — Unfair competitive methods and special privileges not sufficient explanation of monopoly power, 393. — The power of combinations as such to maintain monopoly prices, 395. — Theoretical reasoning on the probable influence of combination and the impossibility of competition, 396. — Consequent necessity of regulation or prohibition, 400. II. Possibility of preventing combination, 402. — Success of certain Federal cases against combinations, 402. — Deterrent effect of more severe penalties, 404. — Reasons for failure of certain trust dissolutions to restore competition, 405. — Possibility of destroying and preventing formal trusts and pools, 408. — Weakness of informal understandings, 410.